Nutritive bambara groundnut powdered drink mix: characterization and in-vivo assessment of the cholesterol-lowering effect - Tan, Wen-Chian; Tan, Choon-Hui; Nyam, Kar-Lin; Tan, Chin-Ping; Julkifle, Advina (Association of Food Scientists & Technologists, 2020)
Drought has become more frequent due to climate change and its effects on the agricultural sector can be devastating. This increases the need for drought tolerant crops such as the Bambara groundnut (BGN) to be farmed in Malaysia. The development of BGN to a product suitable for consumers in this region has not been studied. Therefore, this research aimed to determine consumer acceptability of a nutritive BGN powdered drink mix using the Just-About-Right (JAR) method. BGN flour was produced by mixing soy powder with 0% BGN powder (0B100S), 10% BGN powder (10B90S), 20% BGN powder (20B80S) and 30% BGN powder (30B70S), respectively. The physicochemical properties of the powdered drink mix and its microbiological changes upon storage for six months were then determined. In addition, in-vivo assessment of the cholesterol-lowering effect of this product was conducted. Sample 10B90S was the most preferred sample among the sensory panellists (overall acceptability = 72%). Sample 10B90S remained stable after six months of ambient storage. Rats fed with sample 30B70S showed the most improvement in blood cholesterol levels. In conclusion, nutritive BGN powdered drink mix exhibited good physicochemical properties and could be useful for food applications.